Physical activities and good nutrition: a close relationship with the treatment and prevention of Alzheimer's disease (Research, Society and Development, 2022)
Alzheimer's disease (AD) is a progressive and fatal neurodegenerative disorder that is manifested by cognitive and memory deterioration, progressive impairment of activities of daily living and a variety of neuropsychiatric symptoms and behavioral changes. In this perspective, despite not having a specific form of prevention, the practice of physical exercises and a good diet, it becomes essential in order to maintain a constant and diversified cognitive stimulation throughout life. The objective of this article is to prove the effectiveness of the practice of physical exercises, combined with good nutrition, in the prevention and treatment of Alzheimer's disease. The present study consists of an integrative exploratory literature review. A bibliographic survey was carried out through electronic searches in nationally recognized databases. Thus, it was possible to conclude that physical exercise becomes beneficial for the prevention and treatment of individuals diagnosed with AD, through different mechanisms of action, mainly due to the increase in neurogenesis in the hippocampus and blood flow in the brain areas, in the hormone secretion, synthesis and release of neurotrophin that contribute to greater neuroplasticity. Regarding food, maintaining a healthy diet is essential to prevent and even treat, preventing the progression of Alzheimer's disease. In this sense, the fat-soluble vitamins (A, E, D, K), C and the B complex, the mineral selenium, fatty acid (such as omega 3) and food rich in fruits, vegetables and fish stand out.